Pengaruh Motivasi Kerja dan Kepuasan Kerja Terhadap Komitmen Organisasi Guru di SMPN XYZ Jakarta Pusat - Ramayanthi, Indrika (Jurnal Ketopong Pendidikan, 2023)
National education system has to be able to guarantee improvement of education quality to overcome challenges found from lifestyle changes in local, national, and global level. Purpose of this research is to analyze influence of work motivation and job satisfaction to teachers’ organizational commitment at SMPN XYZ Central Jakarta. Work motivation and job satisfactionis assumed to increase teachers’ organization commitment at SMPN XYZ Central Jakarta. Research methodology used is quantitative method for analyzing influence of work motivation and job satisfaction of teachers to organization commitment at SMPN XYZ Central Jakarta. Regression analysis is a research to identify level of relation between two variables or more without changing, alternation, or manipulation on available data. Sample collected out of 30 teachers as research respondents by questionnaire inputs later become source of analysis. Research concludes there is significant influence between variable working motivation (X1) and variable organization commitment (Y) and also between variable Job Satisfaction (X2) to variable organization commitment (Y).